2023
DOI: 10.3390/antiox12122093
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of the Antioxidant Constituents in Chebulae Fructus Based on an Integrative Strategy of UHPLC/IM-QTOF-MS, MS/MS Molecular Networking, and Spectrum-Effect Correlation

Xiangdong Wang,
Jian Xu,
Li-Hua Zhang
et al.

Abstract: An integrative strategy of UHPLC/IM-QTOF-MS analysis, MS/MS molecular networking (MN), in-house library search, and a collision cross-section (CCS) simulation and comparison was developed for the rapid characterization of the chemical constituents in Chebulae Fructus (CF). A total of 122 Constituents were identified, and most were phenolcarboxylic and tannic compounds. Subsequently, 1,3,6-tri-O-galloyl-β-d-glucose, terflavin A, 1,2,6-tri-O-galloyl-β-d-glucose, punicalagin B, chebulinic acid, chebulagic acid, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For instance, in clinical research, the efficacy of Jiebai Wan pills made with the flesh of CF has been found to be obviously superior to that of the pills made with the whole CF fruits [33]. Furthermore, our previous study revealed that whole-fruit preservation before processing and extraction was beneficial for the conservation of the active tannic ingredients in CF, such as CHG and CHN [34]. Accordingly, we speculated that the tannic constituents undergo certain degradation during collection, preservation, and processing prior to being prescribed in a clinical setting.…”
Section: Distribution Of the Observed Constituents In Different Medic...mentioning
confidence: 99%
“…For instance, in clinical research, the efficacy of Jiebai Wan pills made with the flesh of CF has been found to be obviously superior to that of the pills made with the whole CF fruits [33]. Furthermore, our previous study revealed that whole-fruit preservation before processing and extraction was beneficial for the conservation of the active tannic ingredients in CF, such as CHG and CHN [34]. Accordingly, we speculated that the tannic constituents undergo certain degradation during collection, preservation, and processing prior to being prescribed in a clinical setting.…”
Section: Distribution Of the Observed Constituents In Different Medic...mentioning
confidence: 99%